Designing composite structures: Lay-up selection - Weaver, P M (Proceedings of the Institution of Mechanical Engineers. Part G, Journal of aerospace engineering, 2002)
Abstract The use of high-performance composite materials of the sort used in the aerospace and Formula 1 industries is becoming more widespread. On one level they are exciting to work with because they give scope for designing the ‘material’ in addition to a ‘structure’ through judicious placement of the ply orientation. Layers are stiff and strong in the fibre direction while weak and compliant in the transverse direction. It is this ability to tailor material properties layer by layer that gives designers huge potential in design. One possible explanation for the prevalent use of quasi- isotropic (‘black aluminium’) carbon composites in structures is the lack of available design tools. Analysis packages exist that will predict performance, but only for a given choice of fibre orientation. Here a design tool is presented that aids selection of fibre orientations. Optimization of laminate fibre angles is difficult for multiple-load cases and objectives since there are many local minima to assess. The alternative approach that is presented here, for flat plates and cylindrical shells, circumvents the need (in the early stages of design) for conventional optimization strategies that often prove difficult and complicated to implement. The basic idea is to build a database that stores appropriate properties of all permutations of lay-up angles for a laminate. Rather than access these properties by a question and answer, black-box technique, a graphical method is proposed. The designer can select viable laminates by first plotting a succession of two-dimensional charts containing relevant properties. Then, using simple on-screen techniques, the number of potential laminates is visually reduced by selecting those with desirable properties. Two case studies are presented to illustrate the selection method. The first concerns the optimization of a spar web, typically found in an aircraft wing structure, while the second concerns the optimization of a cylindrical shell, subject to axial compression, that undergoes simultaneous Euler-type buckling and local buckling.